BALANCED SCORECARD REIMAGINED: STRATEGI MULTIDIMENSI UNTUK KINERJA, KBERLANJUTAN, DAN TRANSFORMASI DIGITAL - Lusy; Hermanto, Yustinus Budi; Yuliana Sri Purbiyati; Monica Candra Tjahjono (ITB AAS Indonesia Surakarta, 2025)
This study synthesizes eight recent articles that repositon the Balanced Scorecard (BSC) from merely a performance measurement tool to a multidimensional, adaptive, and strategically relevant management system in the digital era. Through a multi-method and interdisciplinary approach, the article demonstrates how BSC has evolved by integrating sustainability aspects (ESG), digital transformation, and various sectoral contexts, including SMEs, the public sector, education, and post-pandemic industries. The findings reveal that the Sustainability Balanced Scorecard (SBSC) has become a more inclusive model, addressing stakeholder interests and responding to market and technological dynamics. This article offers not only theoretical contributions, by combining BSC, ESG, contingency, and dynamic capabilities theories; but also practical implications for managers, academics, and system developers to adopt a more flexible, measurable, and sustainable strategic framework.